Household Cooking Energy Security Through On-Farm Fuels - World Agroforestry Centre; Leibniz Centre for Agricultural Landscape Research (International Food Policy Research Institute, 2021)
This dataset is generated from the study comparing the cooking performance of on-farm produced fuels such as wood from Gliricidia sepium (Jacq.) Kunth ex Walp. and Cajanus cajan (L.) Millsp. (pigeon pea stalks) with the off-farm fuelwood species Mimusops obtusifolia (Lam. Sapotaceae). Fuel performance was tested using Three-Stone Fire stoves and artisan-made Improved Cooking Stoves. 75 cooking tasks, cooking a standardized pre-defined meal with two pots were completed in five villages in Chamwino and Kongwa districts, Dodoma region. The Controlled Cooking Test design assessed four key performance indicators: (1) time until water is boiling in pot A, (2) time until food item in pot A is ready to be consumed, (3) total cooking time per meal, including food items in pots A and B, (4) total fuel consumption per meal, including food items in pots A and B.